Pathological findings in the first case of caprine paratuberculosis (Johne's disease) in Elazig - Karadas, E; Metin, N; Yaman, I (Scientific Technical Research Council Turkey, 2000)
Caprine paratuberculosis (Johne's disease) was diagnosed according to pathomorphological findings in a 5-year-old indigenous female hairy goat in Elazig. Diagnosis was confirmed by demonstration of Mycobacterium avium subspecies paratuberculosis (M.a. paratuberculosis) in the intestinal smears and tissue sections stained with the Ziehl-Neelsen (ZN) method, and also detection of specific M.a. paratuberculosis DNA by the Polymerase Chain Reaction (PCR).
Keywords: pathomorphological findings; paratuberculosis; goat; Elazig